HAPPINESS AT WORK: THE ROLE OF WORK ENGAGEMENT, JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Setyawan, Yonathan; Aryono, Marcella Mariska; Srimulyani, Veronika Agustini (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
The Creating a sustainable workplace is not only about reducing the impact of pollution on the environment but also about management support in creating a workplace that supports employee happiness and well-being. This study aims to determine the role of job satisfaction, organizational commitment, and work involvement in increasing happiness at work and impact of happiness at work on improving organizational citizenship behavior in PT INKA (Persero) employees. The research subjects used were employees at PT INKA (Persero), totaling 103 employees. The data collection tools used were scales of job satisfaction, organizational commitment, work involvement, and happiness at work. Data analysis used IBM SPSS 22 software for normality tests, reliability tests, and descriptions of respondents' answers, and Lisrel 8.70 software for validity and reliability tests of instruments and hypothesis testing. The results showed that work engagement, job satisfaction, and organizational commitment significantly increased happiness at work, which in turn can increase organizational citizenship behavior in PT INKA (Persero) employees. Happiness at work felt by individuals will have a positive impact both at the individual level (work engagement, job satisfaction, affective commitment) and the organizational level (performance, such as OCB).